مكانة الظَّنِّ من الاستدلال في علوم الأصول قراءةٌ معرفيَّةٌ = The role of probability in argumentation of the usul-sciences: an epistemological study = Peranan kebarangkalian sebagai hujah dalam ilmu-ilmu usul, satu kajian epistemology - Hamawiya, Adham (IIUM Press, International Islamic University Malaysia, 2018)
أكثر ما يتميز به الفكر اليوناني إنتاجُه مجموعة الأبحاث المنهجية العقلية التي أودعها أرسطو كتبًا ثمانية سمَّى مجموعها (الأورغانون)، وبه يتميز العلم اليقيني مما ليس يقينًا، فكأنه المعيار للعلوم كلها، ومن خلاله ناقشت الفلسفة اليونانية موضوعاتها، أي: الإنسان، والطبيعة، والإله، فحاولت إثارة المشاكل فيها، وإيجاد الحلول لها من خلال النظر العقلي الخالص، ثم تُعورف في الثقافة الإسلامية على تسمية هذا المجموع (المنطق)، ولم ترُق المنهجية اليقينية التي يتطلَّبها لعلماء الأصول من فقهاء ومتكلمين ونحويين؛ متقدِّميهم وبعض متأخِّريهم، فهاجموها، وبيَّنوا خطأها، وسعوا إلى إقامة منطق إسلامي جديد في جوهره، فنظروا في أخصِّ ما للمنطق اليوناني، وأرادوا مناقضته والاعتراض عليه، فإذا كانت المنهجية اليقينية سمة المنطق اليوناني؛ فإن المنهجية الظنية سمة المنطق الإسلامي؛ عنها صدر الأصوليون في استدلالاتهم، ومن ثم أسَّسوا معرفيًّا للظن في الفكر الإسلامي؛ ليُمثل منهجية أصولية مركزية مُميِّزة إياه، وعليه؛ تتحرى هذه القراءة بيان مكانة الظن من الاستدلال في علم الأصول؛ بقسميه الاستقراء والقياس، وما يتعلق بهما؛ أي التعليل. *********************************************************** Most of the Greek thought can be characterized as projections of rational methodologies which were put together in "the Organon" by Aristotle. As a standard for all sciences, rational methodologies are used to distinguish the certain from the probability. Through it, the Greek philosophers discussed subjects such as the human, nature, and God. They tried to raise objections, and find solutions through pure rational contentions. Then this methodology was introduced in the Islamic culture with a collective name al-Mantiq. It did not live up to the certainty methodology required by the scholars of the principles of Fiqh, Kalam, and Grammarians. The early and some of the later usul-scholars criticized this methodology, and pointed to its mistakes and sought to establish Islamic Logic new in essence. They looked at the Greek Logic in particular, intending to oppose and object on it. If the methodology of certainty is one of the features of Greek Logic, then the methodology of probability is the feature of the Islamic Logic. From it the usul-scholars derived their evidences, and from it they established an epistemology for probability in Islamic thought in order to represent the central distinct usuli-methodology. Therefore this study investigates to explain the position of probability in the usul science, in its two categories induction and syllogism, and its sister concepts such as causality.